Evaluation Of Collaborative Local Government Post Revitalization of Area Banten Lama Tourism - Ahmad Sururi; Budi Hasanah (Department of Public Administration, 2023)
The purpose of this study is to discuss how the evaluation of local government cooperation is based on the approach to the dimensions of the process and capacity of local government cooperation after the revitalization of the Banten Lama Tourism Area, Serang City. The research method used is a qualitative descriptive approach using data collection techniques through observation, and direct interviews through the Forum Group Discussion (FGD). The number of informants as many as nine people who come from government and non-government elements. Data analysis techniques were conducted through an interactive model: data condensation, data presentation and conclusion. The results of the study indicate that the overall evaluation of local government cooperation had been effective. This can be seen from the level of achievement of trust that is built between the government and the government and the community is increasing, this is supported by a commitment to each activity process that shows a fairly good indication even though there are still problems and normative obstacles such as authority and differences in perspectives between local communities and local communities. government, lack of community participation and spatial planning of Tourism Support Areas (KPW) which is still not optimal. on the otherhand the political will of each regional head in cooperating is quite good, this is evidenced by the existence of a memorandum of understanding that divides the authority of each regional government in each area of Banten Lama